2011
DOI: 10.1136/gutjnl-2011-300767
|View full text |Cite
|
Sign up to set email alerts
|

Induction of dsRNA-activated protein kinase links mitochondrial unfolded protein response to the pathogenesis of intestinal inflammation

Abstract: Objective Inflammatory bowel diseases (IBDs) feature multiple cellular stress responses, including endoplasmic reticulum (ER) unfolded protein responses (UPRs). UPRs represent autoregulatory pathways that adjust organelle capacity to cellular demand. A similar mechanism, mitochondrial UPR (mtUPR), has been described for mitochondria. ER UPR in intestinal epithelial cells (IECs) contributes to the development of intestinal inflammation, and since mitochondrial alterations and dysfunction are implicated in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
161
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(171 citation statements)
references
References 63 publications
9
161
0
1
Order By: Relevance
“…It has been suggested that discordant responses that have previously been recorded between the differently targeted PKR transgenic animals [23,24], could be the consequence of residual peptides that may be expressed in each animal. However, the demonstration by He et al [5] of the relative equivalence of the response in BMDM isolated from either mouse, argues against this explanation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that discordant responses that have previously been recorded between the differently targeted PKR transgenic animals [23,24], could be the consequence of residual peptides that may be expressed in each animal. However, the demonstration by He et al [5] of the relative equivalence of the response in BMDM isolated from either mouse, argues against this explanation.…”
Section: Discussionmentioning
confidence: 99%
“…These pathways sense unfolded protein stress in a compartment‐specific manner, and signal to the nucleus for induction of the expression of unfolded protein response (UPR) genes, which are essential for proteostasis (Schinzel & Dillin, 2015). Mitochondrial unfolded protein response (mtUPR) is activated in response to a variety of mitochondrial stress factors including accumulation of unfolded proteins in the mitochondrial matrix (Rath et al., 2012), imbalance between mitochondrial DNA (mtDNA)‐encoded and nuclear‐encoded electron transport chain (ETC) components (Nargund, Pellegrino, Fiorese, Baker & Haynes, 2012; Yoneda et al., 2004), and perturbation of mitochondrial physiology through inhibition of ETC function or accumulation of reactive oxygen species (ROS) (Nargund et al., 2012; Yoneda et al., 2004), and ensures mitochondrial proteostasis by inducing a vigorous transcriptional response that promotes folding, limits import, and reduces translation of mitochondrial proteins (reviewed in Hill & Van Remmen, 2014; Jensen & Jasper, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial unfolded protein response and the role of CLPP seem to be conserved in mammals (Benedetti et al., 2006; Zhao et al., 2002), where activation of JNK/c‐JUN pathway leads to the expression of transcription factor C/EBP‐homologous protein (CHOP), which, together with C/EBP, mediates the transcription of mtUPR genes (reviewed in Hill & Van Remmen, 2014). It is important that, in addition to inducing transcription of over 400 genes, mtUPR in yeast, C. elegans , and mammals are associated with phosphorylation of eukaryotic initiation factor 2 alpha (eIF2a) by general control nonderepressible 2 (GCN2), resulting in global suppression of translation while mRNAs that contain upstream open reading frames (uORFs) are preferentially translated (Delaney et al., 2013; Rath et al., 2012). Transcriptional activation of mtUPR genes and translational suppression seem to be mediated by two parallel mechanisms, both requiring CLPP (Aldridge et al., 2007; Benedetti et al., 2006; Haynes et al., 2007; Zhao et al., 2002) and reviewed in (Jensen & Jasper, 2014; Schulz & Haynes, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the role of GCN-2 in C. elegans , dsRNA-activated protein kinase (PKR), also known as eukaryotic translation initiation factor 2-α kinase 2 (EIF2AK2), mediates phosphorylation of eIF2α, thus attenuating protein translation in the cytosol during UPR mt in mammalian systems (Fig. 2) (Rath et al, 2012). Interestingly, PKR together with ClpP is also required for the activation of c-Jun, the transcriptional regulator of CHOP (Rath et al, 2012).…”
Section: Reviewmentioning
confidence: 99%
“…2) (Rath et al, 2012). Interestingly, PKR together with ClpP is also required for the activation of c-Jun, the transcriptional regulator of CHOP (Rath et al, 2012).…”
Section: Reviewmentioning
confidence: 99%